An Autologous Platelet‐Rich Plasma Stimulates Periodontal Ligament Regeneration. Issue 11 (1st November 2013) - Anitua, Eduardo; Troya, María; Orive, Gorka
Abstract : Background: Regeneration of periodontal tissues is one of the most important goals for the treatment of periodontal disease. The technology of plasma rich in growth factors provides a biologic approach for the stimulation and acceleration of tissue healing. The purpose of this study is to evaluate the biologic effects of this technology on primary human periodontal ligament fibroblasts. Methods: The authors studied the response of periodontal ligament cells to this pool of growth factors on cell proliferation, cell migration, secretion of several biomolecules, cell adhesion, and expression of α2 integrin. Cell proliferation and adhesion were evaluated by means of a fluorescence‐based method. Cell migration was performed on culture inserts. The release of different biomolecules by periodontal ligament fibroblasts was quantified through enzyme‐linked immunosorbent assay. The α2 integrin expression was assessed through Western blot. Results: This autologous technology significantly stimulated cell proliferation, migration, adhesion, and synthesis of many growth factors from cells including vascular endothelial growth factor, thrombospondin 1, connective tissue growth factor, hepatocyte growth factor, and procollagen type I. The α2 integrin expression was lower in plasma rich in growth factor–treated cells compared to non‐stimulated cells, although no statistically significant differences were observed. Conclusion: This plasma rich in growth factors exerts positive effects on periodontal ligament fibroblasts, which could be positive for periodontal regeneration.